(untitled) (Albayan Scientific Journal, 2023)
Abstract: Most Libyan cities are suffering from the weakness or ignorance the Environmental knowledge and awareness for treatment of solid wastes, absence the strategies of waste management and disposal, and absence of modern scientific implementations. The main objective of this study is to evaluate the Environmental awareness among Libyan families to treat, manage, and dispose the solid wastes, which may have Environmental health and economic impacts, as well as its effects on the beauty of the city. This study was conducted in the Al-Laithi region in city of Benghazi in 2019, where a questionnaire surveyed (66) randomly selected samples of families living within the city. Our results suggested that there was a low level in Environmental education and awareness in the treatment of solid wastes and that the municipality did not participate in providing containers specifically designated for solid wastes with about (69.7%). We also noticed that residents are disposing solid wastes randomly in public squares and roadsides (more than 69.7% of residents), and the emission of unpleasant odors in the area was determined to be approximately (65.2%). The percentage of residents who use shopping bags not designated for collecting solid wastes exceeded (62.1%). Our findings suggested number of considerations and recommendations regarding environmental consciousness and awareness. Keywords: (Environmental awareness, Solid wastes, Tocra)